The motivational effect of multicolored dental restoration on dental behavior of first preliminary school children - Lojain Abdulaziz Melebari; Seba Essam Attas; Abla Arafa (Wiley, 2019)
Abstract Objectives To assess the motivational effect of multi‐colored restoration on the anxiety level of pediatric patients at thedental clinic and its motivational effect on their oral hygiene status. Material and methods A total of 30 participants. Results Both groups revealed reduction in the anxiety level and improvement in their behavior at the dental office but did not reach significance. Plaque index showed a significant reduction per group and a near significance as compared between test groups. Conclusions The use of the multicolored restoration could provide a potential advantage to improve the oral health status of children and might aid in enhancing their behavior at dental clinic particularly younger age groups.